Impelentasi Model Pembelajaran Kooperatif Example Non Example untuk Meningkatkan Hasil Belajar Matematika Tentang Satuan Waktu Kelas III SD Negeri Bugangan 03 Semarang - Ismariyono Ismariyono (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
The problem that the Class III teacher at SD N Bugangan 03 complained about in Mathematics was the low score in Mathematics, especially on the Unit of Time. This is evidenced by the holding of an initial test of students' abilities in learning Mathematics regarding